The fairer sex: male/female differences in architects' use of colour when designing. (9th March 2020) - Tucker, Richard; Motamed, Bahareh
This paper considers if the gender of architects, as one aspect of their cultural indoctrination, impacts their colour use. In other words, it considers if colour use in architectural design is gendered via a process of cultural indoctrination that is influenced by the attitudes towards gender, principally in relation to the biological sex binary, that are prevalent in the cultural contexts that shape us. A survey of 274 designers asked: does gender affect an architect's general attitude towards three dependant variables: 1) colour use; 2) colour preferences; 3) use of colour when designing? It was found that while female architects perceived colour to be more important to architecture than males did, females' portfolios are significantly less colourful. Gender differences were also found for hue preference, dominant colour use and the use of colours for building exteriors. The findings provide the design community with more information about the relationship between culture and colour responses and highlight how gender values may, via colour use, impact architectural design. The authors argue for an approach to design education that acknowledges the potency of architects' subjective tendencies in relation to objective design influences such as the brief or the physical context of a building.